2022
DOI: 10.3389/fgene.2022.1065546
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a prognostic model based on ferroptosis-associated genes in head and neck squamous cancer

Abstract: Ferroptosis is that under the action of ferrous iron or ester oxygenase, unsaturated fatty acids highly expressed on the cell membrane are catalyzed to undergo lipid peroxidation, thereby inducing cell death. In this study, we used ferroptosis marker genes to identify 3 stable molecular subtypes (C1, C2, C3) with distinct prognostic, mutational, and immune signatures by consensus clustering; TP53, CDKN2A, etc. Have higher mutation frequencies in the three subtypes. C3 has a better prognosis, while the C1 subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…High expression of this gene was favorable for the prognosis of patients with HPV+ HNSCC [30]. JCHAIN, PGLYRP4 and SPINK6 had been reported as protective factors for HNSCC patients, consistent with the results in this study [31][32][33].…”
Section: Discussionsupporting
confidence: 90%
“…High expression of this gene was favorable for the prognosis of patients with HPV+ HNSCC [30]. JCHAIN, PGLYRP4 and SPINK6 had been reported as protective factors for HNSCC patients, consistent with the results in this study [31][32][33].…”
Section: Discussionsupporting
confidence: 90%
“…Although they did a great work, their research included merely 400 samples and lacked external validation. Meanwhile, Wei et al [ 62 ] identified genes associated with ferroptosis prognostic score by weighted correlation network analysis (WGCNA) and LASSO, and further constructed a clinical prognostic model of ferroptosis-related prognostic risk score (FPRS). However, their research did not pay much attention to the function of score-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…After screening and lasso regression analysis, eight genes were determined to be related to prognosis. A prognostic model with score related to ferroptosis was nally constructed, which re ected the risk and positive prognostic factors of patients with head and neck squamous cell carcinoma 51 . The role of ferroptosis related to drug resistance in TNBC, however, has not been fully elucidated 52,53 .…”
Section: Discussionmentioning
confidence: 99%